TEACHER PROFESSIONAL DEVELOPMENT AS AN EFFORT TO IMPROVE TPACK SKILLS IN 21ST CENTURY LEARNING - Lina Novita, Tustiyana Windiyani, Deddy Sofyan (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2022)
This article aims to explain the conception and evaluation of information and communication technology (ICT) professional development processes for the development of teacher technology pedagogical content knowledge for 21st century learning. This study emphasizes the involvement of teachers using TPACK in learning. Research is concerned with the use of ICT in learning, setting design goals, redesigning, implementing, and evaluating, as well as reflecting on student learning outcomes. The research approach uses surveys and descriptive analysis. Data triangulation techniques based on observations and interviews with respondents. The results showed that the skills of using technology in learning related to TPACK had a positive effect on teacher confidence in the knowledge of technology pedagogic content for 21st century learning. Five of the seven design teams were able to make pedagogical changes towards 21st century learning, and six teams realized an increase in learning outcomes student. The conclusion of the study stated that TPACK had an impact on learning and teacher confidence in learning.